One health approach on serosurvey of anti-Leptospira spp. in homeless persons and their dogs in South Brazil - do Couto, Anahi Chechia; Gravinatti, Mara Lucia; Pellizzaro, Maysa [UNESP]; Kmetiuk, Louise Bach; Yamakawa, Ana Carolina [UNESP]; da Silva, Evelyn Cristine [UNESP]; Felipetto, Laís Giuliani; Langoni, Hélio [UNESP]; de Souza Leandro, André; de Santi, Carlos Eduardo; dos Santos, Andrea Pires; Biondo, Alexander Welker (Elsevier, 2022)
Although leptospirosis has been described as a worldwide bacterial zoonosis primarily affecting vulnerable populations, to date no study has focused on concomitant serosurvey of homeless persons and their dogs. The aim of the present study was, to use a One Health approach to serologically assess homeless persons and their dogs in 3 major cities of south Brazil (São Paulo, Curitiba, and Foz do Iguaçu). Environmental information was obtained with an epidemiological questionnaire given to all participants. A total of 200 human and 75 dog samples were tested for anti-Leptospira spp. antibodies to thirty different serovars using the microscopic agglutination test. None of the homeless persons were positive while 5 of the 75 (6.7%) dogs were positive. Among homeless population, 89% (177 of 200) were male, 61% (122 of 200) self-declared Non-white, and 67% (134 of 200) were educated up to the 8th school grade. Lower exposure of homeless persons to Leptospira spp. in the present study when compared to other vulnerable populations (slum and low-income residents) may be result of less direct exposure as they are able to rapidly change locations in response to flooding events. In addition, these results may reflect the effectiveness of a specific healthcare service provided to people living in the streets in the 3 cities. While dogs may be used as environmental sentinels for leptospirosis, the low seropositivity results found in this report may indicate low transmission risk to homeless owners in direct daily contact with their dogs.
Keywords: Epidemiology; One health; Social vulnerability